Application of clinical techniques relevant for glaucoma assessment by optometrists: concordance with guidelines. (7th August 2014) - Jamous, Khalid F.; Kalloniatis, Michael; Hayen, Andrew; Mitchell, Paul; Stapleton, Fiona J.; Zangerl, Barbara
Abstract Purpose Guidelines for the screening, prognosis, diagnosis, management and prevention of glaucoma were released by the Australian National Health and Medical Research Council in 2010. Comparable guidance has been made available by respective bodies in the USA and UK at a similar time. Key to successful translation of guidelines into clinical practice includes clinicians having the necessary skills to perform required tests. Optometrists in Australia and New Zealand were invited to participate in an online survey exploring these aspects. The results provide insights for improving glaucoma diagnosis and management by optometric primary eye care practitioners. Methods An online questionnaire was developed to investigate glaucoma assessment of optometrists as a function of demographic details, educational background and experience. Key points to ascertain compliance with current guidelines were the availability of equipment, procedural confidence in techniques, and preferences in visual field tests. Chi square statistics was employed to support similarity to national averages and highlight differences between the two countries. Multivariate linear regression analysis identified variables significantly associated with individual tests being available to optometrists and their confidence in applying them. Results Thirteen per cent of all Australian and 36% of the New Zealand optometrists responded to the survey in 2013, which reflected the demographics/geography of the practising populations. Techniques considered essential or preferred for glaucoma assessment were widely available in both countries with the exception of gonioscopy and pachymetry. After correcting for availability, regression models highlighted therapeutic endorsement and knowledge of glaucoma guidelines as the main variables to maintain high diagnostic confidence. Correlations to number of years in optometric practice mirrored a changed emphasis in teaching and technology over the past 10–15 years. Conclusions Australian and New Zealand optometrists were well equipped to perform glaucoma assessments with the possible exception of gonioscopy. Advanced imaging modalities were not yet fully integrated into optometric practice, although optical coherence tomography has shown use by 23–32% of optometrists. A marked increase in use, availability and procedural confidence of gonioscopy and other techniques with therapeutically endorsed optometrists demonstrates the advantage and importance of additional training.